THE IMPACT OF ARTIFICIAL INTELLIGENCE DEVELOPMENT AND AUTOMATION ON THE LABOR MARKET IN THE DIGITAL ECONOMY - Khaitov, Oxunjon Nomoz ugli; Jakhonova, Odina (THE INNOVATION ECONOMY, 2026)
This article analyzes digital technologies, economic systems, economic indicators, and the impact of artificial intelligence on the labor market, including its positive and negative aspects, as well as new trends emerging in the modern economy. In particular, it examines automation processes that lead to the reduction of certain professions, the emergence of new jobs and specialties, and changes in skill requirements for the workforce. It also highlights the importance of developing digital skills, retraining programs, and lifelong learning systems.